Eco-Beneficial Biocontrol Agents for Mitigating Rice Blast and Enhancing Growth and Yield - Sayera khatun; Mst. Habiba Tamanna; Md Mahmodol Hasan (Universitas Sebelas Maret, 2026)
Rice blast disease, caused by Magnaporthe oryzae, is a major threat to global rice production. Eco-friendly biocontrol agents offer a sustainable alternative to chemical fungicides for managing this disease. This study evaluated 8 biocontrol agents for rice blast management and plant growth promotion under controlled conditions. The antagonistic activity of selected biocontrol agents against M. oryzae was assessed through in vitro assays, followed by in vivo evaluation of disease incidence and severity, plant physiological traits, biomass accumulation, and yield components across 3 consecutive cropping seasons. Among the tested agents, Pseudomonas aeruginosa (SB3) exhibited the strongest antagonistic activity, inhibiting the mycelial growth of M. oryzae by 94.24% in vitro. Consistently, it significantly (p ≤ 0.05) reduced disease incidence (6.67%) and severity (1.11%) under greenhouse conditions, whereas the control treatment showed 20% disease incidence and 4.17% disease severity. Furthermore, application of P. aeruginosa (SB3) significantly enhanced plant growth traits and leaf chlorophyll content, and had a remarkable positive effect on yield contributing characters and rice grain yield (increased by 27.37% over the control). Bacillus velezensis (RB4) also produced favorable results across most evaluated parameters; however, its effects were comparably lower than those of SB3. Overall, this study provides evidence that P. aeruginosa (SB3) is a promising biocontrol candidate that can enhance rice yield, supporting its potential application in sustainable and eco-friendly rice production.